Pelaksanaan Penanganan Tindak Pidana Perdagangan Orang Dalam Lintas Batas Di Wilayah Hukum Pulau Rupat - Eko Saputra; Fitri Wahyuni; Jamri (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2026)
Cross-border human trafficking is a transnational crime that frequently occurs in border areas, including Rupat Island, which is directly adjacent to the Malacca Strait and serves as one of the vulnerable routes for human smuggling and trafficking, with geographical conditions characterized by numerous unofficial small ports and minimal surveillance along unregistered routes contributing significantly to the prevalence of this practice. This study aims to examine the implementation of handling cross-border human trafficking crimes within the legal jurisdiction of Rupat Island and to identify the obstacles faced by law enforcement officers in the handling process, with the problem formulations being how the implementation of handling cross-border human trafficking crimes is carried out within the jurisdiction of Rupat Island and what obstacles are encountered in its implementation. This study employs a sociological (empirical juridical) legal research method with a descriptive qualitative approach, where data were collected through field studies, including interviews with law enforcement officials (Police, Immigration, and related agencies), as well as literature studies on relevant laws and regulations, particularly Law Number 21 of 2007 concerning the Eradication of the Criminal Act of Trafficking in Persons. The findings indicate that the implementation of handling cross-border human trafficking crimes in the jurisdiction of Rupat Island has not been optimally carried out, attributed to limited human resources and surveillance facilities, the vast and difficult-to-monitor maritime area, lack of inter-agency coordination, and low legal awareness among the local community, so that strengthening inter-agency coordination, improving border surveillance infrastructure, and conducting legal awareness programs for the community are necessary to reduce the incidence of human trafficking crimes in the region.